(untitled) (ModaPalavra e-periódico, 2020)
This article examines the impact of the side effects of b reast cancer treatment on women’s self - image. Qualitative and descriptive research was used, c omplemented with field research with thre e women with breast cancer as a sample. After analyzing the data, it was possible to verify that there are impacts on wom en’s self - image, especially when t he side effects of the treatments begin to be felt